Improvement of Minimum KIA Service Standards through Participation of Health Care Community Groups, Lumajang District - Farianingsih Farianingsih; Sri Wahyuningsih (KHD-Production, 2021)
The Community Cares for Health or abbreviated as KMPK is a forum that is an important slice of thepuzzle of an embodiment of governance in the health sector. The main idea is to provide a facilitatorbetween the service provider (supply side) and the service user (demand side) to create an increasein the quality of health services at the Public health services, especially during the pandemic. Thepurpose of the study: to improve services at the Public Health Center during the pandemic with theKMPK innovation. Research method: is descriptive through the KMPK program in 2020 internalevaluation indicators and external evaluation indicators). Results: there was an increase in Publichealth services activities throughout Lumajang Regency from before and after 2020. The increase inactivities assessed from an internal evaluation by the KMPK towards JPP and Rekomtek (coveringthe achievement of the realization of the Service Improvement Promise, the number of publiccomplaints, problems, and obstacles as well as solutions that have been implemented) taken). Meanwhile, the external evaluation was carried out by the Health Office using the Meeting method to evaluate the activities that had been carried out and the obstacles faced as well as the selected alternative solutions (including childbirth by health workers and births by traditional birth attendants, IMD achievements and exclusive breastfeeding achievements, Community Satisfaction Index). Conclusion: Through this KMPK innovation, provides significant added value to the improvement/improvement of services at Public health services throughout Lumajang Regency quickly, precisely, and according to community expectations.